PENGARUH KOMPETENSI, DISIPLIN KERJA DAN PENGALAMAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDAPATAN, PENGELOLAAN KEUANGAN DAN ASET DAERAH KOTA PALU - Sartika, Amwiarni (Katalogis, 2015)
The objectives of this research are to know and analyze the effects of competency, job discipline and work experience simultaneously and partially on personnel performance at Regional Office of Income, Financial Management and Asset Palu City. This study involves 141 respondents that have been determined using censusmethod sampling. Analysis technique used in this research is multiple linier regressions. The results show that competency, job discipline and work experience simultaneously and partially perform significant effects on personnel performance at Regional Office of Income, Financial Management and Asset Palu City. Determination coefficient which is indicated by adjusted R square 0.577 meaning that 57.7% personnel performance in Regional Office of Income, Financial Management and Asset Palu City is affected by competency, job discipline and work experience and 42.3% is affected by other variables that are not investigated in this research.